2018
DOI: 10.1111/imr.12644
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokines in T‐cell memory in health and disease

Abstract: Upon stimulation with their cognate antigen, naive T cells undergo proliferation and differentiation into effector cells, followed by apoptosis or survival as precursors of long-lived memory cells. These phases of a T-cell response and the ensuing maintenance of memory T cells are shaped by cytokines, most notably interleukin-2 (IL-2), IL-7, and IL-15 that share the common γ chain (γ ) cytokine receptor. Steady-state production of IL-7 and IL-15 is necessary for background proliferation and homeostatic surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 214 publications
(302 reference statements)
7
135
0
Order By: Relevance
“…Interleukin-7 (IL-7), which is mainly produced by stromal cells in primary and secondary lymphoid organs, such as bone marrow stromal cells, thymic epithelial cells, fibroblastic reticular cells, and lymphatic endothelial cells, and IL-7 receptor (IL-7R), consisting of a commonchain (CD132) and an IL-7R-specific -chain (CD127), are crucial for CD4 + T-cell homeostasis due to promotion of survival, proliferation, and de novo production of T cells. 56,57 It has been reported that in In contrast, they found positive associations between baseline CD127 density on CD4 + T cells and an increase in CD4 + RTE cell counts and naïve CD4 + T-cell counts after 2 years of effective ART, indicating that CD127 expression on CD4 + T cells is a predictor of increased thymic output after 2 years of suppressive ART. 60 Furthermore, a few studies have found that in INRs, plasma levels of IL-7 were elevated and CD127 expression both on CD4 + and CD8 + T cells was decreased; however, there was no statistically significant correlation between the baseline plasma IL-7 level and absolute CD4 + T-cell count after successful ART.…”
Section: Cytokinesmentioning
confidence: 91%
See 1 more Smart Citation
“…Interleukin-7 (IL-7), which is mainly produced by stromal cells in primary and secondary lymphoid organs, such as bone marrow stromal cells, thymic epithelial cells, fibroblastic reticular cells, and lymphatic endothelial cells, and IL-7 receptor (IL-7R), consisting of a commonchain (CD132) and an IL-7R-specific -chain (CD127), are crucial for CD4 + T-cell homeostasis due to promotion of survival, proliferation, and de novo production of T cells. 56,57 It has been reported that in In contrast, they found positive associations between baseline CD127 density on CD4 + T cells and an increase in CD4 + RTE cell counts and naïve CD4 + T-cell counts after 2 years of effective ART, indicating that CD127 expression on CD4 + T cells is a predictor of increased thymic output after 2 years of suppressive ART. 60 Furthermore, a few studies have found that in INRs, plasma levels of IL-7 were elevated and CD127 expression both on CD4 + and CD8 + T cells was decreased; however, there was no statistically significant correlation between the baseline plasma IL-7 level and absolute CD4 + T-cell count after successful ART.…”
Section: Cytokinesmentioning
confidence: 91%
“…Interleukin‐7 (IL‐7), which is mainly produced by stromal cells in primary and secondary lymphoid organs, such as bone marrow stromal cells, thymic epithelial cells, fibroblastic reticular cells, and lymphatic endothelial cells, and IL‐7 receptor (IL‐7R), consisting of a common γ‐chain (CD132) and an IL‐7R‐specific α‐chain (CD127), are crucial for CD4 + T‐cell homeostasis due to promotion of survival, proliferation, and de novo production of T cells . It has been reported that in HIV‐1‐infected individuals, a decreased percentage of CD127 + CD4 + T cells and an increased percentage of CD127 + CD8 + central memory T cells are associated with incomplete immune reconstitution .…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
“…IL-4 and IL-13 mediate signaling through phosphorylation of signal transducer and activator of transcription (STAT) 6 11,12 but typically not of STAT5 and STAT3, whereas STAT5 and STAT3 become activated with g c cytokines and granulocyte colony-stimulating factor (G-CSF). 13 In type 2 immunity, during certain helminth infections in mice, recruitment of neutrophils contributed to early containment of the parasite during its migration through the lungs. 14 Yet in the same model neutrophils also caused increased damage to the lungs.…”
mentioning
confidence: 99%
“…γ c (also known as CD132, encoded by the Il2rg gene) is a shared receptor subunit of the cytokines IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21 [50]. Il2rg was found in both fishes and birds.…”
Section: The Evolution Of Il-4 and Il-13mentioning
confidence: 99%